2017
DOI: 10.5152/turkthoracj.2017.16025
|View full text |Cite
|
Sign up to set email alerts
|

Diffusely Increased Splenic Fluorodeoxyglucose Uptake in Lung Cancer Patients

Abstract: OBJECTIVES:This study aimed to investigate the association of diffuse splenic F-18 fluorodeoxyglucose (FDG) uptake on positron emission tomography/computed tomography (PET/CT) with tumor maximum standardized uptake value (SUVmax), presence of distant metastases, and hematological and inflammatory parameters. MATERIAL AND METHODS:Initial FDG PET/CT of 15 lung cancer patients with diffuse splenic FDG uptake were retrospectively analyzed (Group 1). Twelve patients who recently underwent FDG PET/CT for histopathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Diffuse splenic uptake is a visual observation on PET/CT corresponding to a global capture of 18 FDG by the organ, relative to liver uptake. This phenomenon, described and used as a potential severity criterion in oncology (11)(12)(13)(14), hardly referred in pyogenic infections (15), has never been reported in IE. In this prospective study, this phenomenon was observed in 24 patients, among them 23 IE (resulting in a specificity of 96%).…”
Section: -Global Splenic Uptakementioning
confidence: 99%
“…Diffuse splenic uptake is a visual observation on PET/CT corresponding to a global capture of 18 FDG by the organ, relative to liver uptake. This phenomenon, described and used as a potential severity criterion in oncology (11)(12)(13)(14), hardly referred in pyogenic infections (15), has never been reported in IE. In this prospective study, this phenomenon was observed in 24 patients, among them 23 IE (resulting in a specificity of 96%).…”
Section: -Global Splenic Uptakementioning
confidence: 99%